Characterization of a slow growing inl+ revertant Neurospora crassa strain. - A. M. Kiss; M. Schablik; A. Zsindely; G. Szabo (Fungal Genetics Reports, 1986)
Characterization of a slow growing inl+ revertant Neurospora crassa strain.